Evaluation of the effect of topical cefadroxil on bacterial load of pathogenic staphylococci in anterior nares in human volunteers, comparative study between oral vs. topical cefadroxil and evaluation of effect of combination of oral plus topical cefadroxil in patients with staphylococcal superficial skin infections - Shah, Tanvi B.; Mehta, Dimple S.; Shah, Hiral A.; Mehta, Sanjay J.; Dave, Jayendra N. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Cefadroxil has good tissue penetration & exerts more sustained action at the site of infection after oral absorption. Our aim of the study was to check topical cefadroxil has any efficacy over staphylococcal superficial skin infection or not. Methods: Pre-treatment nasal swabs were obtained from 25 healthy human volunteers and bacterial load was recorded. After single application of topical cefadroxil 3% in left anterior nare and placebo (vehicle) in right anterior nare nasal swabs were obtained and results were compared. 150 patients with staphylococcal superficial skin infections were distributed in 4 groups: Group A - oral cefadroxil 500 mg twice daily for 5 days, Group B - topical cefadroxil (0.5 % to 5%) twice daily, Group C - cefadroxil 500 mg orally plus placebo (vehicle) topically twice daily and Group D -cefadroxil 500 mg orally plus cefadroxil preparation topically twice daily. Bacterial load was measured before treatment, on follow up &after clinical cure and results were compared. Results: Topical cefadroxil significantly reduced bacterial load after single application in anterior nare. Topical cefadroxil cured and significantly reduced bacterial load in staphylococcal superficial skin infections within 3 days of treatment. Oral plus topical cefadroxil combination therapy significantly reduced bacterial load and cured infection within 3 days of treatment in patients with moderate to heavy bacterial growth. No any adverse effect was observed during entire study period in any of groups. Conclusions: Topical preparation of cefadroxil is safe and effective in treating staphylococcal superficial skin infections. Combination of oral plus topical cefadroxil showed synergistic effect in infections with moderate to heavy growth. This study is registered at CTRI [REG ID: CTRI/2013/02/003433 REF: REF/2013/02/004576].